14-3-3 Proteins: Novel Pharmacological Targets in Neurodegenerative Diseases. (April 2021) - Pair, F. Sanders; Yacoubian, Talene A.
Abstract : 14-3-3 proteins are a family of proteins expressed throughout the body and implicated in many diseases, from cancer to neurodegenerative disorders. While these proteins do not have direct enzymatic activity, they form a hub for many signaling pathways via protein–protein interactions (PPIs). 14-3-3 interactions have proven difficult to target with traditional pharmacological methods due to the unique nature of their binding. However, recent advances in compound development utilizing a range of tools, from thermodynamic binding site analysis to computational molecular modeling techniques, have opened the door to targeting these interactions. Compounds are already being developed targeting 14-3-3 interactions with potential therapeutic implication for neurodegenerative disorders, but challenges still remain in optimizing specificity and target engagement to avoid unintended negative consequences arising from targeting 14-3-3 signaling networks. Highlights: Continuing evidence demonstrates the role of 14-3-3 proteins in common neurodegenerative disorders, including Parkinson's disease and Alzheimer's disease. To date, targeting protein-protein interactions (PPIs, ), such as those used by 14-3-3 proteins, has proven difficult, but emerging methodologies may provide unique ways of targeting 14-3-3 PPIs. Recent advances in targeting 14-3-3 interactions have identified several compounds that can act as double agents to promote certain PPIs while simultaneously disrupting other PPIs. Rational drug design using X-ray crystallography along with computational molecular modeling techniques can lead to more potent and specific 14-3-3 PPI compounds.